Модель вдосконалення організаційно-технологічних рішень у проектах реконструкції (нового будівництва) з урахуванням можливої зміни властивостей матеріалу - Бобраков, А. А. (Ways to Improve Construction Efficiency, 2012)
The model of organizational decision-making process in the management system of resource allocation in reconstruction projects (new construction), taking into account possible changes in material properties. Consider the organization of resource allocation in construction projects including the loss of quality of the material with an appropriate formulation of the problem of optimizing the efficiency of resource and calendar schedule.